Dietary responses to processed and non-processed peanuts and grains by growing-finishing pigs - T F Balogun; B A Koch (Kansas Agricultural Experiment Station Research Reports, 1976)
Twenty-four crossbred barrows and gilts averaging 92 lbs. were used to evaluate whole shelled peanut as a protein and energy source for pigs. Pigs used whole peanuts and corn less efficiently than ground peanuts and corn. Feed intake and average daily gain were greatly improved when peanuts and corn were fed in ground form. Roasting peanuts for one hour at 120 C improved performance only slightly over raw peanuts. Pigs fed a soybean meal diet had slightly better average daily gain than those fed a lysine-supplemented peanut meal diet.; Swine Day, Manhattan, KS, November 11, 1976
Keywords: Swine day; 1976; Kansas Agricultural Experiment Station contribution; no. 519-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 283; Swine; Barrows; Gilts; Peanuts; Growing-finishing pigs